Role of plerixafor in autologous stem cell mobilization with vinorelbine chemotherapy and granulocyte-colony stimulating factor in patients with myeloma: a phase II study (PAV-trial). Issue 3 (March 2015) - Schmid, Andrea; Friess, Dorothea; Mansouri Taleghani, Behrouz; Keller, Peter; Mueller, Beatrice U.; Baerlocher, Gabriela M.; Leibundgut, Kurt; Pabst, Thomas
Abstract: Current practice in Switzerland for the mobilization of autologous stem cells in patients with myeloma is combining vinorelbine chemotherapy and granulocyte-colony stimulating factor (G-CSF) cytokine stimulation. We prospectively investigated adding intravenous plerixafor to the vinorelbine/G-CSF combination (VGP), and compared it with vinorelbine/plerixafor (VP) and G-CSF/plerixafor (GP) combinations. In a final cohort (VP-late), plerixafor was given on the first day of CD34 + cells increasing to > 15 000/mL peripheral blood. Four consecutive cohorts of 10 patients with myeloma were studied. We observed that intravenously administered plerixafor can be safely combined with vinorelbine/G-CSF. VGP was superior in mobilizing peripheral stem and progenitor cells compared to the three double combinations (VP, GP and VP-late), and GP mobilized better than VP. Our data indicate that the triple combination of VGP is an efficient strategy to collect autologous CD34 + cells, with G-CSF contributing predominantly in this concept. Plerixafor can be safely added to G-CSF and/or vinorelbine chemotherapy.